Temperature, accumulation rate, and layer thinning from the South Pole ice core (SPC14) - Buizert, Christo; Conway, Howard; Epifanio, Jenna; Fudge, T. J.; Jones, Tyler R.; Kahle, Emma; Koutnik, Michelle; Morris, Valerie; Schauer, Andrew; Steig, Eric J.; Stevens, Max; Vaughn, Bruce; et al. (IEDA: US Antarctic Program Data Center, 2020)
Abstract: This data set provides the input and output data used in Kahle et al. 2020 to reconstruct climate variables at the South Pole. The files below include high resolution water isotopes, water isotope diffusion length, and various reconstructions of temperature, accumulation rate, and thinning function for the SPC14 ice core. An inverse approach was used to combine information from water isotope diffusion length, Dage, and annual-layer thickness to solve for temperature, accumulation rate, and thinning function. Corrections were applied to account for the advection of ice from upstream to yield estimates for the South Pole site.